2019
DOI: 10.3390/brainsci9050106
|View full text |Cite
|
Sign up to set email alerts
|

Can Evaluative Conditioning Change Well-Established Attitudes Towards Popular Brands? Your Brain Says Yes Even Though Your Mouth Says No

Abstract: In the present study, using both implicit and explicit measures, we addressed the issue of whether strongly developed relationships towards brands could be modified through the use of evaluative conditioning. Using an online survey, individual participant brand lists were created, and formed the basis of this experiment. Participants were then exposed to conditioning during a longitudinal study. Throughout the experiment, a combination of explicit and implicit measures was used to assess changes in attitude. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
1
9
1
Order By: Relevance
“…Our results suggest that the EC-based intervention effectively strengthened the semantic association between MP-food and the healthiness concept, supporting the notion that the early component of the N400 is a suitable index showing the change of associations between food and food-related information (Ma et al, 2014;Blechert et al, 2016;Hoogeveen et al, 2016;Pergola et al, 2017). Indeed, ERPs have been recognized as a useful measure to assess the impact of evaluative conditioning that is not reflected in responses which were measured by explicit ratings and the IAT (Bosshard et al, 2019).…”
Section: Neural Signature Of Semantic Congruency and Associative Lear...supporting
confidence: 78%
See 1 more Smart Citation
“…Our results suggest that the EC-based intervention effectively strengthened the semantic association between MP-food and the healthiness concept, supporting the notion that the early component of the N400 is a suitable index showing the change of associations between food and food-related information (Ma et al, 2014;Blechert et al, 2016;Hoogeveen et al, 2016;Pergola et al, 2017). Indeed, ERPs have been recognized as a useful measure to assess the impact of evaluative conditioning that is not reflected in responses which were measured by explicit ratings and the IAT (Bosshard et al, 2019).…”
Section: Neural Signature Of Semantic Congruency and Associative Lear...supporting
confidence: 78%
“…Importantly, the evidence of EC effects is mainly based on behavioral tasks, with no reference to the neural underpinnings of such effects in the domain of food evaluation and food choice. Neural imaging techniques, especially electroencephalography (EEG) has been recognized as a useful tool in measuring the impact of evaluative conditioning on the change of attitude towards brand names that are not reflected in verbal responses measured by explicit and implicit behavioral paradigms (Bosshard, Koller, & Walla, 2019). Thus, the present study aims to fill these gaps by examining the neural processing underlying the effect of EC in changing food-related semantic associations.…”
Section: Associative Learning Food Associations and Food Choicesmentioning
confidence: 99%
“…Consumer neuroscience tools can be used to investigate the emotional component underling brand evaluation and choice, for example, differences between two similar brands (e.g., Pepsi vs. Coke) (Ma et al, 2007 , 2008 ; Lucchiari and Pravettoni, 2012 ; Reimann et al, 2012a , b ; Pop et al, 2013 ; Al-Kwifi, 2016 ; Guo et al, 2018 ). Bosshard et al ( 2016 ) used EEG to test whether or not liked and disliked brands are further associated with different motivational aspects. The findings of this study suggest that liked brands elicited significantly more positive going waveforms (late positive potentials) than disliked brands over right parietal cortical areas.…”
Section: Main Applications In Marketingmentioning
confidence: 99%
“…Thus, to further investigate the cognitive and emotional components underlying evaluative conditioning for pro-environmental behavior change, we propose for future research to apply neurophysiological measurements to the proposed framework. For example, Bosshard et al (2019) conditioned (dis-)liked brand names with (un-)pleasant sounds and observed that while there were no changes in explicit liking of the brands, variations were observed in neural measures: EEG frontal asymmetry increased for disliked brands when coupled to pleasant sounds and similarly decreased for liked brands that were coupled to unpleasant sounds. Moreover, differences in event-related potentials were observed after extensive sessions of evaluative conditioning ( Kuchinke et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%